Using Established Medical Criteria to Define Disability: A Proposal to Amend the Americans with Disabilities Act - Mark A. Rothstein; Serge A. Martinez; W. Paul McKinney (Washington University Law Quarterly, 2002)
Part II of this Article traces the legislative history of the coverage provision of the ADA and of its predecessor statute, the Rehabilitation Act of 1973. It also explores the conceptual underpinnings of the statutory scheme of attempting to cover only individuals with severe disabilities. Part III analyzes the major cases involving coverage under the ADA, including the trilogy of 1999 Supreme Court cases. It traces the consequences of the Court’s decisions as reflected in the subsequent lower court decisions and their devastating effects on individuals with disabilities. Part IV contains a proposed amendment to the ADA to clarify the definition of “individual with disabilities.” Under the amendment, Congress would authorize the Equal Employment Opportunity Commission (EEOC), after notice and comment rulemaking, to publish medical standards for determining when the most common physical and mental impairments are severe enough to be covered under the ADA. The ADA would presumptively cover an individual whose condition meets the criteria; it would presumptively not cover an individual whose condition does not meet the criteria. Either party could rebut the presumption with clear and convincing evidence that, in light of the particular individual’s overall medical condition, the impairment was or was not a substantial limitation of a major life activity. This approach provides greater certainty to all parties and saves time and money in litigation. Part V provides a demonstration of the feasibility and utility of this approach. After selecting several of the impairments most commonly at issue in ADA cases, the Article reviews the medical literature for each condition. It then distills the medical criteria already used in the clinical setting to distinguish mild or moderate medical conditions from ones that constitute a substantial limitation of a major life activity. Only the latter conditions would be presumptively covered under the proposed amendment of the ADA. Besides the practical advantages of the amendment, it is consistent with the original intent of the ADA: prohibiting discrimination against individuals with substantially limiting disabilities without imposing an undue burden on employers, government entities, and providers of public accommodations. Although the Article focuses on employment, the definition of disability applies to all of the titles of the ADA.
Keywords: Discrimination against people with disabilities in employment; Medical jurisprudence; Law -- Interpretation & construction; Disability evaluation; Employment discrimination; Americans with Disabilities Act of 1990